2021
DOI: 10.1371/journal.pntd.0009645
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous anthrax associated with handling carcasses of animals that died suddenly of unknown cause: Arua District, Uganda, January 2015–August 2017

Abstract: Background Anthrax is a zoonotic disease that can be transmitted to humans from infected animals. During May–June 2017, three persons with probable cutaneous anthrax were reported in Arua District, Uganda; one died. All had recently handled carcasses of livestock that died suddenly and a skin lesion from a deceased person tested positive by PCR for Bacillus anthracis. During July, a bull in the same community died suddenly and the blood sample tested positive by PCR for Bacillus anthracis. The aim of this inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…Members of the affected community reported that they had experienced a long dry season, lasting over 6 months (November 2017–April 2018) without rainfall [ 17 ]. In preparation for the rainfall, a central valley dam was constructed on 28 February–2 March 2018 in Rupyani village for water harvesting; both cows and goats reportedly drank water from the reservoir provided by the dam.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the affected community reported that they had experienced a long dry season, lasting over 6 months (November 2017–April 2018) without rainfall [ 17 ]. In preparation for the rainfall, a central valley dam was constructed on 28 February–2 March 2018 in Rupyani village for water harvesting; both cows and goats reportedly drank water from the reservoir provided by the dam.…”
Section: Resultsmentioning
confidence: 99%
“…These factors were present most likely influencing the anthrax outbreak in both animals and humans. Previous investigations of outbreaks in Uganda that have been done recently also found the association of anthrax to handling of meat from animals that died suddenly [ 4 , 6 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cases were adult males, consistent with the majority of adult males working in livestock slaughtering and livestock product processing. Vegetative forms of Bacillus anthracis are easily killed during normal cooking, but spores are much more resistant to adverse conditions and require heating to at least 100 °C for 15 min for inactivation [ 15 ]. Most of the livestock products have been recovered and destroyed, and those sold are cooked food, so there were no gastrointestinal anthrax cases identified.…”
Section: Discussionmentioning
confidence: 99%
“…We also made several recommendations to the local government, livestock anthrax which could be prevented by animal vaccination. Effective herd immunity against anthrax in cattle requires at least 80% of the animals in an area to be vaccinated [ 15 ]. During an outbreak, all livestock in areas around the affected area should be vaccinated, routinely vaccinate livestock from now on.…”
Section: Discussionmentioning
confidence: 99%
“…Humans at higher risk are predominantly in anthrax-enzootic areas and working in close proximity to livestock, or handling animal tissues [2,54,62]. Economically disadvantaged groups that eat fallen or sick livestock are at particular risk for ingestional anthrax [27,39].…”
Section: Risk Groupsmentioning
confidence: 99%